Comparative study on morphometrics of Callosobruchus maculatus and Callosobruchus chinensis developed on mung bean - Saurabh Singh; Brajrajsharan Tiwari; Rakesh Pandey (Discover Agriculture, 2024)
Abstract Callosobruchus maculatus and Callosobruchus chinensis (Coleoptera:Chrysomelidae) are the two predominant species of pulse beetle, found in India, which are generally wrongly identified. Both species are the most economical insect-pest of pulses and can cause huge quantitative losses. Both are sexually dimorphic and can be differentiated based on some morphological characteristics. The culture of both species was maintained separately at 27 ± 10C and 65 ± 5% RH in the laboratory and the observations on morphometry of various developmental stages viz., egg, larval, pupal and adult male and females were analyzed. During storage, both species develop independently, therefore, the interspecifics of C. maculatus and C. chinensis (first case: C. maculatus ♀ and C. chinensis ♂, second case: C. chinensis ♀ and C. maculatus ♂) were tried to develop. In the first case, females of C. maculatus laid very minute eggs all the eggs could not hatch to develop larvae it showing that the eggs of intersex were infertile. However, in the second case there were no eggs produced by the female C. chinensis.